ALLAH, KONSELOR DAN KONSELI: TRILOGI NARASI DALAM KONSELING PASTORAL - Setiawan, David (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2024)
A major issue in conventional counseling is its limitation in integrating a deep spiritual dimension. This approach often focuses solely on psychological and emotional aspects, thus failing to fully help clients understand and restore themselves in their relationship with God, others, and themselves. To address this challenge, this research explores pastoral counseling as an approach that offers uniqueness through the integration of theological and spiritual principles. This research employs a qualitative approach with a literature review method, emphasizing content analysis to gain a comprehensive understanding of the topic under investigation. This research finds that pastoral counseling is unique compared to general counseling due to the presence of a narrative trilogy consisting of God, counselor, and client, which must be present in the counseling process for it to be more effective. In pastoral counseling, the counselor and client are placed in an equal relationship involving the presence of God through His Spirit in honest and open conversation. This process consists of three stages: preparation, conversation, and evaluation-solution, which are built through the narratives of God, counselor, and client. With the principles of God's Word and the work of the Holy Spirit, as well as the care and love of the counselor, the counseling atmosphere becomes alive and helps clients to know themselves, others, and God correctly. This pastoral counseling allows clients to narrate their lives honestly, thus having the opportunity to experience holistic recovery.